Paradigm of Historical Thinking : Alternative Strategies for Utilizing Historical Thinking Skills in Implementing Independent Curriculum - Kuwoto, M. Ari; Yulifar, Leli; Ma'mur, Tarunasena; Saripuddin, Didin; Supriatna, Encep (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2024)
The three objectives of this research are to: (1) organize history learning utilizing the Merdeka curriculum for historical thinking skills; (2) refine the Merdeka curriculum for historical thinking skills; and (3) serve as an assessment of historical thinking abilities. activities for teaching and learning history that rely on critical thinking. In this work, a case study methodology is combined with a qualitative method. Teachers, students, records, curricula, and historical thinking abilities are the informants that provide the data. Activities for teaching and learning in history classes do not adhere to the standards of assessment. Nonetheless, educators have made an effort to follow certain guidelines and execute their own curricula as precisely as they can. Applications of the Merdeka Curriculum can be modified to take into account historical thinking abilities in the context of teaching history. The study's findings indicate that: (1) Teachers plan the history lessons in the Independent Curriculum; and (2) History lessons are implemented in a way that closely aligns with student achievement. (3) The autonomous curriculum's learning principles are not followed in the learning process. Additionally, there are less situational learning and monotonous learning strategies. (4) There are multiple instances in which the Independent Curriculum-based teaching and learning evaluation principles are not followed in the execution of the evaluation of teaching and learning activities.